Intencionalidade, consciência e caridade nas obras éticas de Pedro Abelardo - Silva, Pedro Rodolfo Fernandes da (2017)
Analyzing the ethical works of Peter Abelard, i.e., Ethica or Scito te Ipsum and Collationes or Dialogus inter Philosophum, Iudaeum et Christianum, it can be said that the Palatine contemplates both the general (theoretical) and particular Ethical orders: his ethical thinking implies a complete analysis in a systematical order. It can be also said that Abelard relied heavily both on the thinkers of the Greek-Roman philosophical tradition, including Aristotle and the Stoics, and on the thinkers of the Christian tradition, among whom Augustine. Departing from this conjunction, Abelard adopts the stoic thesis of the moral indifference of acts to affirm that agent’s intention (intentio) is the only criterion for moral determination. Beyond that, he adopts as the best habit of the soul the Aristotelian notion of virtue, only reached by a great effort and constancy of action. Notwithstanding, this notion seems to contradict moral indifference of acts: despite how great or constant might be the effort to act in a way, this act itself will never be moral per se. This shows how problematic can be the assimilation of traditions assumed by Abelard: stablishing “charity”, source of all virtues, as the fundamental law for moral experience, Abelard interiorizes morality in the individual conscience or mind. In such way, the Aristotelian notion of virtue has nothing but an authoritative value in Abelard’s argument, while charity becomes the good intention that, through the judgment of reason, estimates the divine will and decides to follow it. Therefore, while Stoic moral interiorization presupposes an Ethic in which the virtue’s meaning and purpose is outside the virtue itself, Abelard internalizes moral life in an individual consciousness, in which charity has its purpose and meaning according to its inner decision about following God's will. In such way, charity as good intention and moral criterion contrasts then current penitential practices, whose objectivity of action was the main basis for both the determination of what’s moral or guilty and the imputations of punishment.